109 EFFICACY COMPARISON OF PROSTACYCLIN ANALOGUE AND PROSTACYCLIN RECEPTOR AGONIST AS THIRD LINE TREATMENT FOR PULMONARY ARTERIAL HYPERTENSION. (15th December 2022) - Dardi, Fabio; Martini, Giulia; Guarino, Daniele; Magnani, Ilenia; Rotunno, Mariangela; Ballerini, Alberto; Bertozzi, Riccardo; Donato, Federico; Manes, Alessandra; Palazzini, Massimiliano; Galiè, Nazzareno
Abstract: Background: Pulmonary arterial hypertension (PAH) is a progressive disease characterized by small pulmonary arteries remodeling that leads to increased pulmonary vascular resistance, dyspnea, fatigue, right heart failure and ultimately death. Prostacyclin analogue drugs, such as epoprostenol or treprostinil, have a vasodilator, antiproliferative and immunomodulatory effect, representing established therapies for cases of severe PAH. Both these drugs improve exercise capacity, functional class and hemodynamic parameters, while epoprostenol also improves survival among patients with PAH. Despite these therapeutic benefits, these treatments need parenteral administration. Recently, the approval of selexipag, an oral selective prostacyclin receptor agonist, may represent a possible alternative option in some PAH patients. Methods: patients with PAH treated as third line therapy with epoprostenol, treprostinil or selexipag, on top of inhibitor of type 5 phosphodiesterases and endothelin-1 receptor antagonists, referred to our center from February 1995 to December 2021 were retrospectively included. All patients noninvasive [6 minutes walking distance (6MWD)] and invasive [mean pulmonary arterial pressure (mPAP), pulmonary vascular resistance (PVR), cardiac index (CI), right atrial pressure (RAP) and mixed venous oxygen saturation (SvO2)] parameters were first collected at the baseline right heart catheterization (prior to the beginning of prostacyclin treatment) and then 3-4 months after the beginning of third line therapy. The absolute improvements in these parameters were compared with Dunn's test. Data are expressed as median (interquartile range). Results: 153 PAH patients treated as third line therapy with epoprostenol, treprostenil and selexipag were included (44, 73, 36 patients respectively). At 3 to 4 months after the beginning of the third line therapy, improvements in the 6MWD were: 65 (25 - 132) m with epoprostenol, 16 (-8 - 63) m with treprostenil and 12 (-10 - 57) m with selexipag (p = 0.044). Absolute RAP reduction was -1 (-4–2.5) mmHg with epoprostenol, -1 (-3 - 2) mmHg with treprostenil and 0 (-4 - 2) mmHg with selexipag (p = 0.953). Absolute PAPm reduction was -5 (-9 - -1) mmHg with epoprostenol, -5 (-11 - -1) mmHg with treprostenil and -6.5 (-14 - 0) mmHg with selexipag (p = 0.670). Absolute CI improvement was 0.9 (0.4–1.1) l/min/m2 with epoprostenol, 0.5 (0.2–0.8) l/min/m2 with treprostenil and 0.3 (0.1 - 1) l/min/m2 with selexipag (p = 0.022). Absolute PVR improvement was -4.5 (-7.6 - -2) WU with epoprostenol, -3.2 (-4.9 - -1.7) WU with treprostenil and -2 (-4.4–0.9) WU with selexipag (p = 0.021). Absolute SvO2 increase was 4.8 (1.7–13.2) % with epoprostenol, 2.6 (-2.2–6.2) % with treprostenil and 2.3 (-2.4–7.5) % with selexipag (p = 0.036). For all three-way significant comparisons, the only pairwise comparisons with a p-value <0.05 were between epoprostenol vs the other two drugs. Conclusions: in our study population, epoprostenol, treprostenil and selexipag improve both exercise capacity and haemodynamic parameters in PAH patients when used as third line therapy, with the highest efficacy in the first group and, possibly, the lowest efficacy in the latter. These results confirm the beneficial role of these drugs in PAH patients and may suggest a possible favorable role for selexipag in the management of PAH patients with a less severe disease reserving a more invasive treatment strategy with parenteral prostanoids in patients with a higher risk disease.